1975
DOI: 10.1159/000117486
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid in the Treatment of Schizophrenias

Abstract: After reviewing the literature on nicotinic acid in the treatment of schizophrenia, the authors present the results of the Canadian collaborative study. The data indicate that nicotinic acid has no therapeutic effect of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In variance with the notion that increased transmethylation is responsible for schizophrenic symptoms are the findings that methyl acceptors such as nicotinic acid at doses up to 3,000 mg daily (Ban and Lehmann, 1975), or butylgallate in doses of 5,000 mg daily {Baldessarini, 1975) do not improve schizophrenia.…”
Section: Transmethylation and Schizophreniamentioning
confidence: 97%
“…In variance with the notion that increased transmethylation is responsible for schizophrenic symptoms are the findings that methyl acceptors such as nicotinic acid at doses up to 3,000 mg daily (Ban and Lehmann, 1975), or butylgallate in doses of 5,000 mg daily {Baldessarini, 1975) do not improve schizophrenia.…”
Section: Transmethylation and Schizophreniamentioning
confidence: 97%
“…In five of these studies the hypothesis was tested that nicotinic acid has a beneficial action over and above the effects achievable by standard treatments; in three studies the therapeutic efficacy of nicotinic acid is presumably facilitated by the administration of ascorbic acid, pyridoxine and d'penicillamine; in three studies, the presence of the 'mauve factor', 'pink spot', or a 'bufotenin-like substance' in the urine as indicators of a favourable therapeutic outcome with nicotinic acid is to be tested; and in one study, that exacerbation of schizophrenic psychopathology, induced by the associated administration of a methyl-donor and a monoamine oxidase inhibitor, can be prevented or counteracted by nicotinic acid administration. The First Progress Report on the CMHA Collaborative Study was presented at the Annual Meeting of the Canadian Psychiatric Association in June 1970 and published by the Canadian Mental Health Association later that year (6). In view of the controversial clinical findings in the first two completed clinical trials (1,24), and in the absence of verified indicators of therapeutic responsiveness, Progress Report I concluded that the practical decision as to whether nicotinic acid should be prescribed must be influenced by consideration of its known adverse effects.…”
Section: Design Of Cmha Collaborative Studymentioning
confidence: 99%
“…In this context it was pointed out that dermatological (flushing, skin rash and dermatitis), gastrointestinal (sialorrhea, heartburn, nausea, vomiting and diarrhea), hepatic (liver function abnormality) and cardiovascular (hypotension, tachycardia and syncope) symptoms were rather commonly associated with high doses of nicotinic acid administration during the first three-and-a-half years of the CMHA Collaborative Study. Progress Report I was followed within eight months by Complementary Report A, which was presented at the Annual Meeting of the Research Directors of the CMHA in 1971, and was published by the Canadian Mental Health Association later that year (5). Based on the negative findings in three out of the first four completed clinical trials, Complementary Report A concluded that nicotinic acid therapy is not the optimal treatment for the average schizophrenic patient.…”
Section: Design Of Cmha Collaborative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the controversy regarding the effectiveness of nicotinic acid treatment the Board of Directors of the Canadian Mental Health Association (CMHA), approximately 6 years ago, set up a series of systematic studies to obtain relevant information on nicotinic acid treatment {Ban, 1971a, b , Ban and Lehmann, 1970).…”
Section: Findings In Clinical Trialsmentioning
confidence: 99%